2017
DOI: 10.24871/1732016155-161
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Hepatitis B Virus Infection in Hemodialysis Patients at Sanglah General Hospital and It’s Risk Factors

Abstract: Background: Patients receiving maintenance hemodialysis (HD) are at higher risk for hepatitis B virus (HBV) infections than in general population. Strict infection control is essential to prevent nosocomial transmission. We aimed to investigate the incidence of HBV infection in the HD population in Sanglah General

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
(39 reference statements)
1
9
1
2
Order By: Relevance
“…Some studies reported that longer duration of HD was a risk factor associated with nosocomial infections [16][17][18][19], while a positive correlation was determined between HABSI and diabetes, number of HD sessions, and length of hospital stay [12]. Risk for a HABSI increased significantly with HbA1c levels above 7% [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies reported that longer duration of HD was a risk factor associated with nosocomial infections [16][17][18][19], while a positive correlation was determined between HABSI and diabetes, number of HD sessions, and length of hospital stay [12]. Risk for a HABSI increased significantly with HbA1c levels above 7% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Risk for a HABSI increased significantly with HbA1c levels above 7% [12]. There were studies which showed a significant relationship between nosocomial infections and age of patients [15,16,18], with HBV infections being more common in relatively younger individuals (mean age: 39.2 ± 14.6 years), while there was a strong relationship between HCV infections and relatively older age group (mean age: 55 ± 12 years) [16,18]. A positive history and number of blood transfusions were both https://doi.org/10.1371/journal.pone.0234376.t002…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations